Basic Ethics For Online Teaching And Learning: The Islamic Perspective - Hazlina Abdullah; Rahimah Saimin,; Saiful Izwan Zainal (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.